Gaya Kepemimpinan dan Motivasi Mempengaruhi Kinerja Pegawai - Nurlina Nurlina; Safrida Safrida; Musmulyadi Musmulyadi; Burhan Burhan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effect of leadership style and motivation on the performance of the employees of the Ministry of Religion of South Sulawesi Province. This research uses a quantitative approach, primary and secondary data sources. Collecting data through field research by means of questionnaires and documentation. As for the population in this study were all employees totaling 232 civil servants. To determine the minimum required sample, the Slovin formula is used. By calculating the sample size, 69 samples were obtained. The analysis technique used is multiple linear regression. The results showed that there was a partially positive and significant influence between leadership style and motivation on employee performance. The most dominant factor of leadership style influences employee performance. Leadership and work motivation are in the good category, and this condition should be maintained and improved. Keywords: Leadership, Motivation, and Performance